Is local wisdom able to build sustainable communities in informal flood-prone settlements? Evidence from Glintung Kampong, Malang City, Indonesia - Sedyowati, Laksni; Yuniarti, Sari; Sufiyanto, Sufiyanto (University of Merdeka Malang, 2023)
This study aims to highlight innovative and sustainable measures in adaptation to climate change and the Covid-19 pandemic through integration into flood control efforts based on empirical data in Glintung Kampong, an informal flood-prone settlement in Indonesia and to explore what local wisdom values influence the success of the measures undertaken. This study was designed to use a mixed method combining qualitative and quantitative data. Qualitative data consists of in-depth interviews, observations, and desk studies. Quantitative data is used for the generalization of some qualitative data across a wider field. The study results show that the existence of drainage channel facilities from the government can trigger creative ideas and innovative measures in the community. Community involvement with their â€œguyub rukunâ€ and â€œgotong royongâ€ values is the most influential factor in determining the success of the program, followed by community leaders, the ability to adapt to flood risk, and the ability to establish good interactions with external parties.